Use of cardiac imaging in chronic coronary syndromes: the EURECA Imaging registry. (1st December 2022) - Neglia, Danilo; Liga, Riccardo; Gimelli, Alessia; Podlesnikar, Tomaž; Cvijić, Marta; Pontone, Gianluca; Miglioranza, Marcelo Haertel; Guaricci, Andrea Igoren; Seitun, Sara; Clemente, Alberto; Sumin, Alexey; Vitola, João; et al.
Abstract: Background: The prospective, multicentre EURECA registry assessed the use of imaging and adoption of the European Society of Cardiology (ESC) Guidelines (GL) in patients with chronic coronary syndromes (CCS). Methods: Between May 2019 and March 2020, 5156 patients were recruited in 73 centres from 24 ESC member countries. The adoption of GL recommendations was evaluated according to clinical presentation and pre-test probability (PTP) of obstructive coronary artery disease (CAD). Results: The mean age of the population was 64 ± 11 years, 60% of patients were males, 42% had PTP >15%, 27% had previous CAD, and ejection fraction was <50% in 5%. Exercise ECG was performed in 32% of patients, stress imaging as the first choice in 40%, and computed tomography coronary angiography (CTCA) in 22%. Invasive coronary angiography (ICA) was the first or downstream test in 17% and 11%, respectively. Obstructive CAD was documented in 24% of patients, inducible ischaemia in 19%, and 13% of patients underwent revascularization. In 44% of patients, the overall diagnostic process did not adopt the GL. In these patients, referral to stress imaging (21% vs. 58%; P < 0.001) or CTCA (17% vs. 30%; P < 0.001) was less frequent, while exercise ECG (43% vs. 22%; P < 0.001) and ICA (48% vs. 15%; P < 0.001) were more frequently performed. The adoption of GL was associated with fewer ICA, higher proportion of diagnosis of obstructive CAD (60% vs. 39%, P < 0.001) and revascularization (54% vs. 37%, P < 0.001), higher quality of life, fewer additional testing, and longer times to late revascularization. Conclusions: In patients with CCS, current clinical practice does not adopt GL recommendations on the use of diagnostic tests in a significant proportion of patients. When the diagnostic approach adopts GL recommendations, invasive procedures are less frequently used and the diagnostic yield and therapeutic utility are superior. Structured Graphical Abstract: Structured Graphical Abstract In the whole population of patients with chronic coronary syndromes (CCS) enrolled in the EURECA registry, 56% of patients were managed according to the 2019 European Society of Cardiology (ESC) Guidelines (GL) for the overall diagnostic process. The adoption of GL recommendations led to a lower proportion of invasive coronary angiograms (15% vs. 48%) and coronary revascularizations (8% vs. 19%). However, when invasive angiograms were performed adopting GL recommendations, 60% showed obstructive coronary artery disease (CAD) (>70% stenosis) and 54% led to revascularization as compared with 39% and 37%, respectively, when the diagnostic process did not adopt the GL recommendations.